Single‐Cell and Spatial Transcriptomics Decodes Wharton's Jelly‐Derived Mesenchymal Stem Cells Heterogeneity and a Subpopulation with Wound Repair Signatures. Issue 4 (11th December 2022) - Chen, Penghong; Tang, Shijie; Li, Ming; Wang, Dezhi; Chen, Caixiang; Qiu, Yiqun; Fang, Zhuoqun; Zhang, Haoruo; Gao, Hangqi; Weng, Haiyan; Hu, Kailun; Lin, Jian; et al.
Abstract: The highly heterogeneous characteristics of Wharton's jelly mesenchymal stem cells (WJ‐MSCs) may be responsible for the poor clinical outcomes and poor reproducibility of treatments based on WJ‐MSCs. Exploration of WJ‐MSC heterogeneity with multimodal single‐cell technologies will aid in establishing accurate MSC subtyping and developing screening protocols for dominant functional subpopulations. Here, the characteristics of WJ‐MSCs are systematically analyzed by single cell and spatial transcriptome sequencing. Single‐cell transcriptomics analysis identifies four WJ‐MSC subpopulations, namely proliferative_MSCs, niche‐supporting_MSCs, metabolism‐related_MSCs and biofunctional‐type_MSCs. Furthermore, the transcriptome, cellular heterogeneity, and cell‐state trajectories of these subpopulations are characterized. Intriguingly, the biofunctional‐type MSCs (marked by S100A9, CD29, and CD142) selected in this study exhibit promising wound repair properties in vitro and in vivo. Finally, by integrating omics data, it has been found that the S100A9 + CD29 + CD142 + subpopulation is more enriched in the fetal segment of the umbilical cord, suggesting that this subpopulation deriving from the fetal segment may have potential for developing into an ideal therapeutic agent for wound healing. Overall, the presented study comprehensively maps the heterogeneity of WJ‐MSCs and provides an essential resource for future development of WJ‐MSC‐based drugs. Abstract : The heterogeneity of Wharton's jelly mesenchymal stem cells (WJ‐MSCs) hampers clinical translation. The authors map a comprehensive single‐cell and spatial transcriptomic atlas to decipher the heterogeneity of WJ‐MSCs, and verify the efficient wound repair capabilities of the S100A9 + CD29 + CD142 + subpopulations, which are more enriched in the fetal segment of an umbilical cord, providing a more targeted way to treat diseases.